Preferences and acceptability of law enforcement initiated referrals for people who inject drugs: a mixed methods analysis - Gabriella K. Olgin; Annick Bórquez; Pieter Baker; Erika Clairgue; Mario Morales; Arnulfo Bañuelos; Jaime Arredondo; Alicia Harvey-Vera; Steffanie Strathdee; Leo Beletsky; Javier A. Cepeda (BMC, 2020)
Abstract Background Law enforcement officers (LEOs) come into frequent contact with people who inject drugs (PWID). Through service referrals, LEOs may facilitate PWID engagement in harm reduction, substance use treatment, and other health and supportive services. Little is known about PWID and LEO attitudes and concerns about service referrals, however. The objective of this mixed-methods study was to examine the alignment of service referral preferences and acceptability among PWID and LEOs in Tijuana, Mexico. Methods We assessed service referral preferences and perceived likelihood of participation in health and social services, integrating data from structured questionnaires with 280 PWID and 306 LEOs, contextualized by semi-structured interviews and focus groups with 15 PWID and 17 LEOs enrolled in two parallel longitudinal cohorts in Tijuana, Mexico. Results Among potential service referral options, both PWID (78%) and LEOs (88%) most frequently cited assistance with drug- and alcohol-use disorders. Over half of PWID and LEOs supported including harm reduction services such as syringe service programs, overdose prevention, and HIV testing. The majority of PWID supported LEO referrals to programs that addressed basic structural needs (e.g. personal care [62%], food assistance [61%], housing assistance [58%]). However, the proportion of LEOs (30-45%) who endorsed these service referrals was significantly lower (p <  0.01). Regarding referral acceptability, 71% of PWID reported they would be very likely or somewhat likely to make use of a referral compared to 94% of LEOs reporting that they thought PWID would always or sometimes utilize them. These results were echoed in the qualitative analysis, although practical barriers to referrals emerged, whereby PWID were less optimistic that they would utilize referrals compared to LEOs. Conclusions We identified strong support for LEO service referrals among both LEO and PWID respondents, with the highest preference for substance use treatment. LEO referral programs offer opportunities to deflect PWID contact with carceral systems while facilitating access to health and social services. However, appropriate investments and political will are needed to develop an evidence-based (integrated) service infrastructure.